- Thread starter
- #1

#### miller1991

##### New member

- Jan 23, 2019

- 2

why is this equation so special it is in standard form, and when i solve for zeros

i factor down to

-1( 2x^2-3x-20)

factor

( 2x^2-3x-20)

factor by grouping 2(-20)=-40 what numbers multiple to equal -40 and add to equal -3

-8(5) = -40

-8+5= -3

and then just to find zeros the next step would be

(x-8) (x+5)

x=8 x=-5

BUT

thats not right apparently the answer is

x=4 x = -5/2

the answer i got here

(x-8) (x+5)

x=8 x=-5

is meant to be -1(2x+5)(x-4)

which gives

x=4 x = -5/2

but like 5+-4 =1 dont even equal -3

apparently if i use the huge equation to solve for zeros that works but

why did (2x+5)(x-4) using this work, and how to i recognize when to use it like that

and i dont even know where they pulled the 5 and -4 from

does anyone know why when solving for zeros

y=-2x^2 +3x+20

is a tricky question

p.s

originally the question was solve zeros for

y=3x+20 -2x^2

but putting it in standard form was easy and i dont think that messes with the final answer

thanks !!!